A new species of Ducetia (Tettigoniidae, Phaneropterinae) from Mindanao, Philippines based on bioacoustics, stridulatory file morphology and genetic data - Salvador, Jewel Anne G.; Nuñeza, Olga Macas; Robillard, Tony; Tan, Ming Kai (Zootaxa, 2024)
The Ducetia japonica species group consists of 11 species widely distributed in Asia and Australia. It includes a single species from the Philippines: Ducetia adspersa Brunner von Wattenwyl, 1878. Previously synonymized under Ducetia japonica (Thunberg, 1815), this species was resurrected for its unique stridulatory file. Based on its distinct stridulatory file morphology, male calling song and cytochrome c oxidase subunit I signature, we discovered and describe here a new species from Mindanao in the south of the Philippines: Ducetia laniae sp. nov. We also describe the calling song of this new species. This discovery underscores the rich biodiversity of the region and highlights the necessity for continued exploration and study to unravel the complexities within this genus.